Takaful (Islamic insurance), risk management and Maqasid Al- Shari‘ah - Sabirzyanov, Ruslan; Hashim, Mohamad Haidir (İstanbul Sabahattin Zaim Üniversitesi, Uluslararası İslam Ekonomi ve Finansı Araştırma ve Uygulama Merkezi, 2015)
Risk presents in the life of a human being from beginning of his/her life until the end. Daily transactions, financial operations are not exceptions from subjects of a risk. Moreover, risk does not differentiate between Islamic and non-Islamic financial transactions. However, the question boils down is “what is view of Islam to a risk and should it be managed and how?” This paper attempts to analyse and examine risk management in takaful from a standpoint of Shar?‘ah objectives. The study is limited to general overview, in other words the paper describes concepts and practices in general without going deep into details. Therefore, qualitative research method was used to analyse risk management in takaful and its relation to the objectives of Shar?‘ah. Findings of this paper are the concepts of risk management in takaful and its relation with Shar?‘ah objectives as it ought to be, as well as disclosure of current practices, issues and challenges to be precise. The study has shown its significance, since there is a lack of literature on this topic. Moreover, this paper shows some issues of current practice of risk management in takaful related to Maqa?id al- Shar?‘ah.

Risk, insan yaşamının başından sonuna dek her alanında mevcuttur. Günlük ticari ve finansal işlemler de riskten azade değildir. Bu demektir ki risk, konvansiyonel ve İslami finans arasında ayrım yapmaz. Böylece ortaya, “İslam’ın riske bakışı nasıldır ve risk nasıl idare edilir?” sorusu çıkmaktadır. Bu makale İslam Hukuku açısından tekaful’deki risk yönetimini inceler. Çalışma genel bir çerçeve ile sınırlandırılmıştır, diğer bir ifade ile ana kavramlar ve uygulamalar derine inilmeden açıklanacaktır. Bu bağlamda, tekafuldeki risk yönetimi ve bunun İslam Hukuku’yla bağlantısı niteliksel bir yöntemle incelenecektir. Bu çalışmanın sonundaki bulgular tekafuldeki risk yönetimi kavramı ve bunun İslam Hukuku’yla bağlantısı, mevcut uygulamaların dökümü ve bunların durumu ve problemleri gibi olacaktır. Bu çalışmanın önemi ve literatüre katkısı, ilgili konu üzerindeki literatür eksikliğinin giderilmesi olacaktır. Özetle, bu makalede tekaful’deki risk yönetiminin pratiğiyle alakalı tespitler İslam’ın Hedefleri bağlamında ifade edilecektir.
Tekaful (islami sigortacılık), risk yönetimi ve islamın hedefleri
RUSLAN SABIRZYANOV AND MOHAMAD HAIDIR HASHIM International Islamic University Malaysia
Keywords: Risk Management; Takaful; Islamic Insurance; Maqasid al-Shari’ah; Risk Yönetimi; Tekaful; İslami Sigortacılık; Research Subject Categories::SOCIAL SCIENCES::Business and economics::Economics